The Histopathology of Urticaria Revisited—Clinical Pathological Study. (October 2017) - Barzilai, Aviv; Sagi, Lior; Baum, Sharon; Trau, Henri; Schvimer, Michael; Barshack, Iris; Solomon, Michal
Abstract : Background: The classic histopathological findings of urticaria include dermal edema and a sparse perivascular infiltrate of neutrophils, eosinophils, macrophages, and lymphocytes. However, this pattern is inconsistently described. Objective: To describe the histological and immunofluorescence characteristics of urticaria and to identify distinctive patterns. Methods: A retrospective study was performed in which the medical files and biopsy specimens of 58 patients with acute and chronic classical urticaria were reviewed. Pathological parameters were quantified. Results: We recognized 2 distinctive patterns of urticaria: lymphocyte and neutrophil predominant; the former was characterized by a perivascular location, whereas the latter was associated with an interstitial location and a denser infiltrate. Mast cells were relatively sparse, better demonstrated with special stains. Tryptase stain demonstrated more mast cells than Giemsa stain. Extravasated erythrocytes were present in 50% of the cases, but vasculitis was not observed. Conclusions: Histological findings in classical urticaria show a spectrum of findings from a sparse superficial perivascular to a deep perivascular and interstitial infiltrate. Distinctive groups based on the dominant cell type can be identified, accounting for the similarity to neutrophilic urticarial dermatosis. Lesions may have a purpuric appearance, but leukocytoclastic vasculitis is never present.